Resource allocation for wireless caching in socially-enabled D2D communications - Huaqing Wu; Li Wang; Svensson, Tommy; Zhu Han (IEEE International Conference on Communications (2003), 2016)
Wireless caching using device-to-device (D2D) communications is a promising approach for reducing delivery delay and improving spectrum efficiency and energy efficiency. In addition to the physical link condition, social behaviors are also of great importance for effectiveness enhancement of the D2D-based wireless caching schemes. In this work, we focus on resource allocation including power and spectrum to improve the system efficiency in terms of jointly considered spectrum efficiency and energy efficiency, by leveraging both physical and social characteristics. Furthermore, a heuristic-based mixed integer nonlinear programming algorithm is proposed to solve the joint optimization problem, including the establishment of D2D links, spectrum allocation and power optimization. Numerical results demonstrate the effectiveness of the proposed scheme in terms of different pairing algorithms.